Analisi dei costi di buprenorfina vs metadone nella terapia dei soggetti con dipendenza da oppiacei - Colombo, Giorgio L.; Faillace, Guido; Ferdico, Michele (Farmeconomia. Health economics and therapeutic pathways, 2003)
In the last decades, methadone has virtually represented the only available option for the treatment of opioid addicts in Italy. Early in the year 2000 buprenorphine has been introduced on the market as a possible alternative to methadone. While most of the research conducted so far in our country has focused on possible differences in clinical outcomes, depending on the pharmacological differences among the two molecules, the economical aspects of the choice between the two drugs have barely been addressed. In this paper we present a pharmacoeconomical comparison between buprenorphine and methadone in the treatment of heroin dependence by the Italian health service, adopting the perspective of the Society. For this purpose, we constructed a decision analysis model comprising the possible clinical pathways a patient can go through following the inclusion in the therapeutic programs of the SerT. Two types of incremental costs have been considered in the model: direct health costs, i.e. drug acquisition and medical staff costs, and indirect cost, due to loss of working hours for the administration of the drug. The analysis was conducted with a cost-minimization approach, mandatory in the absence of reliable data on clinical differences, and with a time perspective of 12 months. Our results indicate that buprenorphine, despite its higher pharmaceutical cost, is the more convenient option for the treatment of opioid dependence in Italy, as it permits a significant saving of productivity losses. The difference in indirect costs relies on the shorter mean treatment time with buprenorphine and on the possibility of reducing dosing frequency, which allows many patients to attend health services only thrice in week, instead of the daily visits to the SerT necessary for most methadone-treated patients. The results were challenged in a series of sensibility analysis conducted on all relevant and uncertain paramenters, and in no case the option methadone resulted more convenient than buprenorphine, confirming the reliability of the results obtained in the base case scenario.